Investigating the role of digital transformation and digital innovation on school performance - Erdawaty Kamaruddin; Ibnu Salman; Nunu Ahmad Annahidl; Munawiroh Munawiroh; Heni Waluyo Siswanto; Imran Siregar; Suprapto Suprapto; Ahmad Habibullah; Dwi Purwoko; Haudid Haudid; Agus Purwanto (International Journal of Data and Network Science, 2024)
This research aims to analyze the relationship between digital transformation and school performance and the relationship between digital innovation and school performance. The research method is quantitative through surveys, research data was obtained by distributing online questionnaires to 489 high school teachers throughout Indonesia who were selected using a simple random method. Data analysis used covariance-based structural equation modelling (CB-SEM) with SmartPLS 4.0 software to analyze research data. The independent variables are digital transformation and digital innovation, and the dependent variable is school performance. The stages of data analysis are validity testing, reliability testing, model fit testing and significance testing of hypothesis testing. The results of this research are that digital transformation has a positive and significant relationship with performance. Moreover, digital innovation has a positive and significant relationship to performance. The findings of this research support and prove the results of previous research that digital transformation has a positive effect on organizational performance and innovation and confirms the direct influence of innovation on organizational performance. The contribution of this research is aimed at various literature related to the role of digital transformation and innovation on organizational performance. Meanwhile, for practical implications, digital transformation and innovation can improve organizational performance, especially in schools.